Improving MSME Performance Through Digital Literacy in the Digital Economy Era - Yusuf Yusuf; Jefri Putri Nugraha (Economics And Business Management Journal ( EBMJ ), 2024)
This study aims to develop a risk management model for network technology projects based on the Certainty Factor (CF). The background of this research is the high complexity and risks often encountered in network technology projects, which impact the timeliness, budget, and quality of outcomes. The research method employed is a quantitative approach through simulation and testing on a network project case study. The results indicate that the CF-based approach enhances accuracy in risk identification and mitigation, providing greater efficiency compared to conventional methods. These findings contribute to offering a systematic framework for project managers to effectively manage risks, particularly in the field of network technology.